EFFECT OF ON MELT GRAFTING OF GLYCIDYL METHACRYLATE ONTO NATURAL RUBBER IN THE PRESENCE OF ORGANIC PEROXIDES - ., Eddiyanto (JURNAL PENELITIAN SAINTIKA, 2011)
The main aim of this work was to study of melt grafting glycidyl methacrylate (OMA) on naturalrubber (NR) using reactive processing methods. Four different peroxides benzoyl peroxide (8PO),dicumyl peroxide (DCP), 2,5-dimethyl-2,5-bis-(tert-butyl peroxy) hexane (T-101 ), and 1, 1-di(tertÂbutylperoxy)-3,3,5-trimethyl cyclohexane (T-29890) were examined as free radical initiators. An appropriate methodology was established and chemical composition and reactive processingparameters were examined and optimised. Procedures for purification of the reaction products weredeveloped so that the extent of monomer grafting on the rubber can be characterised accurately, usingmainly FTIR technique. The reaction mechanism of the functionalisation was also examined. It wasfound that the grafting degree of GMA increased with increasing of GMAs concentration. It was alsofound that T-101 was a suitable peroxide to initiate the grafting reaction of these monomers on NR.